(3GdEOGQI GdESJQGJjLjI deYGgOI GdEOGQI (B:s (3ChQGb hhbGFY fOhI GdEOGQI GdESJQGJjLjI deYGgOI GdEOGQI (B/s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 1999)
(3JCKjQ GdeJZjQGJ GdHjFjI Ydi GdJOQjH GdEOGQj(B- (3JWHjb JMdjd (BSWOT- (3Ydi eYGgOI GdJOQjH(B- (3UjGZI GdNWW GdESJQGJjLjI hHQGeL JMSjf GdLhOI(B- (3GdJNWjW GdESJQGJjLj aj feGPL eNJdaI deYGgOI GdJOQjH(B- (3ebheGJ GdJfajP GdaYGd ddESJQGJjLjI hOhQ GdQbGHI hGdJbhje aj JfajP GdNWW GdESJQGJjLjI(B- (3NHQGJ hQDi EVGajI(B- (3hQTI Yed eTQhYGJ LeGYjI(B.s
Keywords: (3GdEOGQIs; (3GdEOGQI GdESJQGJjLjIs; (3GdEOGQI GdYGeIs